Evaluasi Efek Samping OBat Kemoterapi terhadap Quality of Life (QOL) Pasien Kanker Payudara di Rumah Sakit X Jakarta - Sondang Khairani; Sesilia A Keban; Meyke Afrianty (Fakultas Farmasi Universitas Pancasila, 2019)
Breast cancer is the number one cancer type discovered at women in the world. Most causes are genetic factors and hormonal factors. One cancer treatments with chemotherapy. Chemotherapy drugs active in cells dividing and reproducing, but cells normally to be affected by chemotherapy and side effects from chemotherapy drugs affect quality of life. The aim of the study to evaluate side effects of chemotherapy drugs on the quality of life of breast cancer patients. Sampling technique observational prospective breast cancer patients with completed the chemotherapy cycle from September 2017 to April 2018 with descriptive analysis and statistics by looking correlation between drug side effects and Quality of Life (QoL). Results of the study were side effects of fatigue 100%, nausea 67,5%, vomiting 60%, no appetite 63,75%, fever 42,5%, joint pain 43,75%, diarrhea 16,25%, difficulty swallowing 16,25%, allergies 5%, itching 1,25%, mouth sores 3,75%, swollen right hand 1,25%, constipation 3,75%. QoL results are physical 6,2%; psychology 5,3%; social 4,9%; spiritual 6,8%. Results of Sperman test showed no correlation between the side effects of chemotherapy and QoL P> 0,05. This study shows that there is no relationship between the side effects drug chemotherapy and QoL in breast cancer patients.